Banding for access related iscaemia : our experience in Kuantan, Malaysia - Othman, Ahmad Faidzal; Abdul Rahman, Mohd Norhisham Azmi (2014)
Since it was first recognized in 1969 by Storey, access related ischaemia has been a significant problem. Reported incidence is between 2-20%. The treatment goals are to reverse the ischaemia and salvage the access. One of the recognized treatment strategies is banding of the fistula. We would like to present our result for the past year in employing this strategy in our local community in Kuantan, Malaysia